You should end up with two equations:

Do you see where these equations come from?

To eliminate one of the variables, the easiest thing to do would be to divide the second equation by the first...

Results 1 to 5 of 5

- March 29th 2013, 09:05 PM #1

- Joined
- Mar 2013
- From
- China
- Posts
- 2

## f(6) = ?

Sorry if this is wrong section, I'm not sure where else to post. I am stuck with this problem:

f(x)= m * 2^{kx}

where

f(3)=27

f(4)=36

Question is: What is f(6)?

I can't figure how to solve either k or m; or how to substitute either of them for something useful. According to my textbook the answer is 64, but I have no idea how to get there. Any help is appreciated.

- March 29th 2013, 09:20 PM #2

- March 29th 2013, 09:22 PM #3

- Joined
- Feb 2013
- From
- Saudi Arabia
- Posts
- 444
- Thanks
- 86

## Re: f(6) = ?

Keuko667

substitute x=4 first to the given relation and find : 36= m 2^(4k),

then substitute again x= 3 and find 27 = m 2^(3k)

divide these two equations and m disapears...you wil get 36/27=2^ k then get the logarithms of both sides to find the value of k .

the last step is to substitute k in one of the two equations and solve it for m ... After all these you know the complete formula of the function substitute x= 6 and find all what you need. As simple as such... try it....

MINOAS

- March 29th 2013, 09:24 PM #4

- Joined
- Feb 2013
- From
- Saudi Arabia
- Posts
- 444
- Thanks
- 86

- March 29th 2013, 09:49 PM #5

- Joined
- Mar 2013
- From
- China
- Posts
- 2